Evaluation of NAVA-PAP in premature neonates with apnea of prematurity: minimal backup ventilation and clinically significant events - Protain, Alison; Firestone, Kimberly; Hussain, Saima; Lubarsky, Daniel; Stein, Howard (Frontiers in Pediatrics, 2023)
Background Neonates with apnea of prematurity (AOP) clinically deteriorate because continuous positive airway pressure (CPAP) provides inadequate support during apnea. Neurally adjusted ventilatory assist (NAVA) provides proportional ventilator support from the electrical activity of the diaphragm. When the NAVA level is 0 cmH2O/mcV (NAVA-PAP), patients receive CPAP when breathing and backup ventilation when apneic. This study evaluates NAVA-PAP and time spent in backup ventilation. Methods This was a prospective, two-center, observational study of preterm neonates on NAVA-PAP for AOP. Ventilator data were downloaded after 24 h. The number of clinically significant events (CSEs) was collected. A paired t-test was used to perform statistical analysis. Results The study was conducted on 28 patients with a gestational age of 25 ± 1.8 weeks and a study age of 28 ± 23 days. The number of CSEs was 4 ± 4.39/24 h. The patients were on NAVA-PAP for approximately 90%/min, switched to backup mode 2.5 ± 1.1 times/min, and spent 10.6 ± 7.2% in backup. Conclusion Preterm neonates on NAVA-PAP had few CSEs with minimal time in backup ventilation.